Practical model for predicting corrosion rate of steel reinforcement in concrete structures - Yu, Bo (2014)
A practical model for predicting corrosion rate of steel reinforcement in concrete structures was proposed. The numerical model with nonlinear boundary conditions for macro cell corrosion of steel reinforcement in concrete structures was established based on electrochemical principles and the Bulter-Volmer equation. The influences of parameters such as anode-to-cathode (A/C)ratio, relative humidity, concrete resistivity, cover thickness on the corrosion control mode and corrosion rate of steel reinforcement in concrete structures were then investigated. Finally, a practical model for predicting corrosion rate of steel reinforcement in concrete structures was proposed based on a comprehensive nonlinear regression analysis with easily quantifiable engineering parameters, such as water-to-cement (W/C)ratio, chloride content, thickness of concrete cover and relative humidity. Model comparison and experimental verification demonstrate that the proposed prediction model is of good accuracy and applicability to real life scenarios in terms of capturing the corrosion behavior of steel reinforcement in different situations.